Is the Church of Sweden an Ordinary' Civil Society Organization? - Linde, Stig (Nordic journal of religion and society, 2018)
This article explores the advocacy activities of the Church of Sweden. The historical co-optation of the Church by the state, a Lutheran theological heritage, and a trend from voice to service within Swedish civil society might discourage stronger political activism by the Church. The following research questions are answered: How does the extent of the advocacy activities of the Church of Sweden, understood as trying to influence politicians and officials and as achieving changes, differ from that of other civil society organizations (CSOs)? What factors explain differences in advocacy activities between the Church of Sweden and the other types of CSOs? How do the types of issues raised by the Church of Sweden through its influence differ from those of other CSOs? The article draws on a large sample (N = 1,150) from a national survey targeting Swedish civil society organizations. It compares the Church of Sweden with other organizations representing diffuse interests (i.e., religious congregations and solidarity organizations) and organizations representing specific interests (i.e., pensioners' organizations). The analysis shows that the historical position of the Church has granted its organizations strength in terms of resources that make them more active in advocacy than comparable organizations representing diffuse interests. The Church of Sweden of the new millennium hence seems to be able to engage more in politics because of, rather than in spite of, its institutional role.